The Development of Macromedia Flash-Aided Interactive Media to Increase the Ability to Understand Fiction Stories Information in Elementary School Students - Anggi Chairunnisa Siregar; Abdurahman Adisaputera; Anita Yus (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to: (1) Analyze the level of effectiveness of Macromedia Flash-assisted interactive learning media in story text learning that will be developed at SD60606 Public Elementary School Medan Perjuangan. (2) Analyzing how the level of interactive learning media assisted by Macromedia Flash on story text learning will be developed in SD60606 Public Elementary School Medan Perjuangan. This study uses the Borg & Gall development research. Based on the analysis of Macromedia Flash assisted learning media products from the experts, it was declared very effective and feasible to use with criteria of the validity of the material experts 85.42%, the design expert 91.00%, and the linguist 85.00%. Based on the completeness data of student learning outcomes before using interactive learning media assisted by Macromedia Flash obtained an average value of 62 while using a large scale completeness reached an average of 90 with a gain score of 0.74 into the high category. And the student questionnaire responses to the effectiveness of Macromedia Flash-assisted interactive learning media reached 90% of 30 students. Based on this data Macromedia Flash-assisted interactive learning media are said to be effectively used in learning with the assumption that students' understanding of story text is higher when using Macromedia Flash-assisted interactive learning media.